SEASONAL VARIATIONS IN MICRO MINERAL PROFILE OF LACTATING KANKREJ COWS (BOS INDICUS) - Lateef, A; Das, Hemen; Panchsara, HH; Sanap, MJ; Nilofar, Haque; Parasani, HR (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Present study reports seasonal variation in concentrations of copper (Cu), zinc (Zn), iron (Fe) and manganese (Mn) in different production groups of lactating Kankrej cows. The concentrations of Cu was significantly higher (p
Keywords: Kankrej; Lactating; Seasons; Serum; Micro mineral